PENGEMASAN PAKET WISATA KEBUGARAN DI DESA SAYAN, KECAMATAN UBUD, KABUPATEN GIANYAR - Hadi, R.R. Hanny Advenia; Sudana, I Putu; Kristianto, Yohanes (Jurnal IPTA (Industri Perjalanan Wisata); Vol 11 No 1 (2023): Jurnal IPTA (July 2023)DO - 10.24843/IPTA.2023.v11.i01.p04, 2023)
Wellness and village tourism are one of the travel trends that can be done during the pandemic. To increase interest in this tour, the activities are packaged in an attractive manner, in this study referring to the thematic packaging of fitness tour packages. This research was conducted to determine the potential of wellness tourism in Sayan Village, which was then packaged thematically to become a fitness tour package. The package of this tour package can then be used as a tourism product in Sayan Village. Data collection techniques used in this study, namely observation, in-depth interviews, and literature study. Then, the data analysis technique in this study used descriptive qualitative analysis. Based on data collection, the results obtained are that there are four dimensions of potential fitness tourism in Sayan Village, including the emotional dimension, spiritual dimension, mental dimension, and environmental dimension. The wellness potention is then packaged into thematic tour packages according to the dimensions of wellness. The package packages include the emotional dimension, Sayan Healing Culture Tour with a full day tour type; spiritual dimension, Sayan Authentic Spiritual Tour with half day tour activity type; mental dimension, Sayan Happy Tour with half day tour activities; and environmental dimensions, Sayan Eco Life Tour with half day tour activities.